The effects of symptom overreporting on PTSD treatment outcome. Issue 1 (9th August 2020) - van Minnen, Agnes; van Dalen, Birgit; Voorendonk, Eline M.; Wagenmans, Anouk; de Jongh, Ad
ABSTRACT: Background: It is often assumed that individuals with posttraumatic stress disorder (PTSD) who overreport their symptoms should be excluded from trauma-focused treatments. Objective: To investigate the effects of a brief, intensive trauma-focused treatment programme for individuals with PTSD who are overreporting symptoms. Methods: Individuals ( n = 205) with PTSD participated in an intensive trauma-focused treatment programme consisting of EMDR and prolonged exposure (PE) therapy, physical activity and psycho-education. Assessments took place at pre- and post-treatment (Structured Inventory of Malingered Symptomatology; SIMS, Clinician Administered PTSD Scale for DSM-5; CAPS-5). Results: Using a high SIMS cut-off of 24 or above, 14.1% ( n = 29) had elevated SIMS scores (i.e. 'overreporters'). The group of overreporters showed significant decreases in PTSD-symptoms, and these treatment results did not differ significantly from other patients. Although some patients (35.5%) remained overreporters at post-treatment, SIMS scores decreased significantly during treatment. Conclusion: The results suggest that an intensive trauma-focused treatment not only is a feasible and safe treatment for PTSD in general, but also for individuals who overreport their symptoms.